Implementasi Sistem Operasi Real-Time pada Arduino Nano dengan media Komunikasi NRF24L01 Untuk Pengukuran Suhu, Kelembaban, dan Intensitas Cahaya - Eka Nanda Sugianto; Wijaya Kurniawan; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In building system node sensor for smart home monitoring needed an operating system so that tasks can be executed simultaneously. By running tasks simultaneously, performance of the system monitoring smart home expected to running properly. If not, then the smart home monitoring system will work improperly such as experiencing a decrease or increase in temperature significantly due to lack of timely processing of data and the delay in making a decision that should not occur in a smart home monitoring system. In addition, the operating system must be in real-time because a smart home monitoring system is expected to be able to make decisions and provide the right information in the actual time. To resolve the above problems, RTOS (Real Time Operating System) is one of the appropriate operating systems in executing tasks simultaneously and it's also real-time. To apply RTOS to the Arduino Nano microcontroller, FreeRTOS library is needed. This sensor node system is divided into 2 node, namely client node and base node. The wireless communication media is using nRF24L01. The client node consists of the Arduino Nano microcontroller, LDR sensor, DHT11 sensor, and nRF24L01. While the base node consists of an Arduino Nano microcontroller and nRF24L01. The number of tasks on the client node is 3 tasks while at the node base is 2 tasks. Implementation for method is using Preemptive Priority Based-Scheduling. From the test results, tasks can run according to the priority given. The vTaskDelay function to set the execution time of each task is running as it should.